Design and Fabrication of Compact MEMS Electromagnetic Micro-Actuator with Planar Micro-Coil Based on PCB - Roer Eka Pawinanto; Jumril Yunas; Burhanuddin Majlis; Azrul Hamzah (Universitas Ahmad Dahlan, 2016)
This paper reports a compact design of electromagnetically driven MEMS micro-actuator utilizing planar electromagnetic coil on PCB (Printed Circuit Board). The micro-actuator device consists of an NdFeB permanent magnet, thin silicon membrane and planar micro-coil which fabricated using simple standard MEMS techniques with additional bonding step. Two planar coils designs including planar parallel and spiral coil structure with various coil geometry are chosen for the study. Analysis of the device involves the investigation of electromagnetic and mechanical properties using finite element analysis (FEA), the measurement of the membrane deflection and functionality test. The measurement results show that the thin silicon membrane is able to deform as much as 12.87 µm using planar spiral micro-coil. Reasonable match between simulation and measurement of about 82.5% has been revealed. The dynamic response test on actuator driven by parallel planar coil shows that silicon membrane effectively deformed in 40 s for an input electrical power of only 150 mW. It is also concluded that planar parallel coil is considered for the simple structure and easy fabrication of the actuator system. This study will provide important parameters for the development of compact and simple electromagnetic micro-actuator system for fluidic injection system in lab-on-chip.